Table of Content - -, (Journal of Islamic Sciences, 2023)
Table of Content1. Apocryphal writings relating to the Old and New Testaments and the Jewish  and Christian position on itMrs. Maha Abdel-Rahman Rahma Al-Shabrami2. The penalty purposes in the Islamic ShariahMr. Basil Ahmad dudeen3. Practical issues in prayer during the Corona pandemicMr. Abdelghaffar Saleh Harbi4. The reality of Imam Al-Mahdi in the light of Islamic ShariahProf. Dil Aqa WAQAR, Prof. Shirzad Azizi5. The concept of monotheism (Tawhid) in the Jewish doctrinesLecturer \ Shorouq Mohammed Al-Tashlan6. Imam Ghazali’s rational approaches in his book Al-Mustasfa – An empirical and analytical study –Dr. Nayef Abdul Rahman Al-Jabr, Mrs. Hind Saad Al-Harbi7. The Impact of Contemporary Issues Jurisprudence (Fiqh al-Nawazil) on Islamic FeminismDr. Fatima Juma Alwhash
Keywords: Journal of Islamic Sciences